2018
DOI: 10.1080/02770903.2018.1437174
|View full text |Cite
|
Sign up to set email alerts
|

The effects of maternal asthma during pregnancy on child cognitive and behavioral development: A systematic review

Abstract: The evidence suggests that the relationship between maternal asthma during pregnancy and poor developmental and behavioral outcomes of children is weak. Children of mothers with well-managed asthma during pregnancy have similar developmental trajectories to those born to healthy mothers. Prospective, longitudinal studies are needed to confirm these conclusions. Optimal asthma management is important in pregnancy as it may have longer term benefits for the health of the offspring. As the rate of asthma increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…A potential confounder of the association between maternal antiasthmatic medication use and subsequent offspring development is the maternal history of asthma during pregnancy . We found no evidence of confounding by a maternal history of prepregnancy asthma, consistent with those of several studies . Furthermore, we examined the effect modification by sex; the results suggested no sex differences regarding the association between in utero antiasthmatic medication exposure and offspring development.…”
Section: Discussionsupporting
confidence: 89%
“…A potential confounder of the association between maternal antiasthmatic medication use and subsequent offspring development is the maternal history of asthma during pregnancy . We found no evidence of confounding by a maternal history of prepregnancy asthma, consistent with those of several studies . Furthermore, we examined the effect modification by sex; the results suggested no sex differences regarding the association between in utero antiasthmatic medication exposure and offspring development.…”
Section: Discussionsupporting
confidence: 89%
“…Changes in infant gut microbiome secondary to maternal immune status may result in changes to infant temperament and sensory features, which could be a potential explanation for our finding of high proportions of distractibility and arrhythmia. A recent systematic review (Whalen et al, 2019) highlights the importance of optimal asthma management during pregnancy, and the potential effect this has on child development. Thus, our findings, along with the previous literature, support the need to further investigate the role of maternal asthma in infant behavioural outcomes.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Both temperament and sensory processing can be assessed reliably in infancy, offering an opportunity to explore early bidirectional links between early developmental vulnerabilities and immune function (Engel-Yeger et al, 2014;O'Connor et al, 2017). Infants born to mothers with asthma have been reported to be at-risk for poorer behavioural outcomes (for review, see Whalen et al, 2019), which may be associated with temperament and sensory differences (Ben-Sasson et al, 2013;Mallise et al, 2020). Exploring differences in temperament and sensory processing of infants born to mothers with asthma during the first year of life may allow for the early identification of those at high-risk of poorer developmental and behavioural outcomes in later childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about short-term placental and fetal manifestations of MIA when the immunogen is targeted to the lungs, as in respiratory infections and maternal airway inflammation [14][15][16][17][18][19][20] , which are common during pregnancy: 49.6% of control mothers in the National Birth Defects Prevention Study reported respiratory infections during pregnancy 21,22 .…”
Section: Introductionmentioning
confidence: 99%